PENGEMBANGAN VIDEO PEMBELAJARAN BERBASIS CANVA PADA MATERI MENYAMBUT USIA BALIGH SISWA KELAS IV : VALIDITAS DAN PRAKTIKALITAS - Manurung, Azhar Azmi; Lestari, Sukma; Al Afif Hazmar; Rian Vebrianto (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
This study aimed to develop of video learning assisted by Canva on puberty awareness for 4th grade student and to determine the validity and practicality of the developed media. The research employed a Research and Developmnet (R&D) approach using the ADDIE development model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included 2 Islamic Education teacher and 30 4th grade students. Data were collected through observation, interviews, questionnaires, and documentation. The research instruments consisted of validation sheets for media and material experts, as well as practicality questionnaires for teacher and students. Data were analyzed using quantitative and qualitative analysis techniques. The results showed that the develop video learning assisted by Canva achieved a very high level of validity, with media expert validation reaching 88,3% and material expert validation reaching 90% both categorized as “Very Valid”. The practicality test results indicated that the media obtained a score of 94,2% from teachers and 92,4% from students, categorized as “very practical”. Based on these findings, it can be concluded that the video learning assisted by Canva on puberty awareness is valid, practical, and feasible to be used as an alternative learning medium to enhance the quality of Islamic Religious Education learning in elementary schools.